1996
DOI: 10.1074/jbc.271.38.23176
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of an Upstream AP-1 Motif for the Constitutive and Phorbol Ester-inducible Expression of the Urokinase-type Plasminogen Activator Receptor Gene

Abstract: Long tracts of CCG trinucleotide or CCGNN pentanucleotide repeats in DNA have previously been shown to resist assembly into nucleosomes. This may provide a molecular explanation for the nature of certain rare, folate-sensitive fragile sites in human chromosomes that contain expanded CCG triplet tracts. Further, it is known that methylation of CpG dinucleotides at or near these fragile sites enhances the fragile phenotype. Here DNAs containing 76 tandem CCG triplets or 48 CCGNN pentanucleotide repeats were meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
150
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 56 publications
5
150
0
Order By: Relevance
“…We previously reported that u-PAR gene expression in cultured colon cancer is largely due to a transcriptional activation of the gene, and diverse cis-elements of the u-PAR promoter were characterized as being essential for this regulation (Wang et al, 1994;Lengyel et al, 1996;Allgayer et al, 1999c). We, therefore, asked as to whether Pdcd4 is able to regulate u-PAR gene expression at the promoter level.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that u-PAR gene expression in cultured colon cancer is largely due to a transcriptional activation of the gene, and diverse cis-elements of the u-PAR promoter were characterized as being essential for this regulation (Wang et al, 1994;Lengyel et al, 1996;Allgayer et al, 1999c). We, therefore, asked as to whether Pdcd4 is able to regulate u-PAR gene expression at the promoter level.…”
Section: Resultsmentioning
confidence: 99%
“…In GEO cells being characterized by high endogenous Pdcd4 and low endogenous u-PAR (Allgayer et al, 1999b;Allgayer et al, 1999c) a siRNA specifically downregulating endogenous Pdcd4 led to a significant increase of activity of a luciferase reporter driven by À398 bp upstream of the main transcriptional initiation site of the u-PAR gene (Figure 3a). The À398 bp corresponds to the basal u-PAR promoter as described previously (Lengyel et al, 1996;Allgayer et al, 1999c). In RKO cells, being characterized by a high endogenous u-PAR promoter activity and u-PAR gene expression (Allgayer et al, 1999a, c), transient transfections with a CAT reporter driven by the À398 bp u-PAR promoter, and increasing amounts of a pdcd4 expression construct, were performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations